2015
DOI: 10.1016/j.jacc.2015.07.050
|View full text |Cite|
|
Sign up to set email alerts
|

Food Consumption and its Impact on Cardiovascular Disease: Importance of Solutions Focused on the Globalized Food System

Abstract: Major scholars in the field, based on a 3-day consensus, created an in-depth review of current knowledge on the role of diet in CVD, the changing global food system and global dietary patterns, and potential policy solutions. Evidence from different countries, age/race/ethnicity/socioeconomic groups suggest the health effects studies of foods, macronutrients, and dietary patterns on CVD appear to be far more consistent though regional knowledge gaps are highlighted. There are large gaps in knowledge about the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
267
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(311 citation statements)
references
References 251 publications
4
267
2
9
Order By: Relevance
“…On the basis of the current evidence, food-based priorities to reduce CVD risk are to increase consumption of whole grains, fruits, vegetables, legumes, nuts and seeds, and fish, to keep a moderate dairy and vegetable oil intake, and to avoid/reduce consumption of refined grains, sugar-sweetened beverages (SSBs), and red and processed (sodium-preserved) meats (Anand et al 2015;Moran et al 2014;Mozaffarian 2016). Thus, the United States Dietary Guidelines (healthy American diet, the Mediterranean diet and the vegetarian diet) (USDA 2015) and scientific societies Eckel et al 2014;Perk et al 2012), for example, recommend dietary patterns that combine these food-based recommendations regarding prevention of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the current evidence, food-based priorities to reduce CVD risk are to increase consumption of whole grains, fruits, vegetables, legumes, nuts and seeds, and fish, to keep a moderate dairy and vegetable oil intake, and to avoid/reduce consumption of refined grains, sugar-sweetened beverages (SSBs), and red and processed (sodium-preserved) meats (Anand et al 2015;Moran et al 2014;Mozaffarian 2016). Thus, the United States Dietary Guidelines (healthy American diet, the Mediterranean diet and the vegetarian diet) (USDA 2015) and scientific societies Eckel et al 2014;Perk et al 2012), for example, recommend dietary patterns that combine these food-based recommendations regarding prevention of chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition labelling has been included by the World Health Organization as an intervention strategy to provide consumers meaningful information on the nutritional content of foods and to help them select more healthier ones [2,3]. One can argue that well-designed food labels, with accurate and easy-to-understand nutrition information, can have the potential to nudge consumers towards informed healthy food choices [4][5][6][7][8]; although, others have suggested that nutrition claims are being used more as marketing tools by industry [8,9]. Moreover, products with nutrition claims on food labels could be perceived as "healthier" by consumers [10].…”
Section: Introductionmentioning
confidence: 99%
“…2 On the basis of the current evidence, the traditional Mediterranean-type diet, including plant foods with emphasis on plant protein sources, provides a well-tested healthy dietary pattern to reduce cardiovascular disease, also in diabetic patients. 3 It has been suggested that a Mediterranean diet down-regulates cellular and humoral inflammatory pathways related to atherosclerosis. 4,5 Vascular homeostasis results from the balance between endothelial damage and repair.…”
Section: Introductionmentioning
confidence: 99%